1991
DOI: 10.1123/jsep.13.3.281
|View full text |Cite
|
Sign up to set email alerts
|

Physical Practice is Superior to Mental Practice In Enhancing Cognitive and Motor Task Performance

Abstract: This study compared varying ratios of physical to mental practice on cognitive (pegboard) and motor (pursuit rotor) task performance. Subjects (36 males and 36 females) were randomly assigned to one of six conditions experiencing different amounts of combined mental and physical practice. Seven practice sessions (four trials per session for the pegboard and eight trials per session for the pursuit rotor) were employed. ANOVA results showed that all treatment conditions, except the pegboard control group, showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1
14

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 10 publications
3
45
1
14
Order By: Relevance
“…Outro procedimento é a utilização do período de pré-teste (com prática física da habilidade) no delineamento (HIRD et al, 1991, STEBBINS, 1968WOHLDMANN et al, 2008). Tais procedimentos podem contribuir para maior assimilação da tarefa, creditando à prática mental os efeitos de aprendizagem que ela não teria.…”
Section: Discussão E Conclusãounclassified
See 1 more Smart Citation
“…Outro procedimento é a utilização do período de pré-teste (com prática física da habilidade) no delineamento (HIRD et al, 1991, STEBBINS, 1968WOHLDMANN et al, 2008). Tais procedimentos podem contribuir para maior assimilação da tarefa, creditando à prática mental os efeitos de aprendizagem que ela não teria.…”
Section: Discussão E Conclusãounclassified
“…O posicionamento da prática mental em relação à prática física é outra variável estudada e também tem sido tradicionalmente testada com prática física e combinação de prática (CAHN, 2008;HIRD et al, 1991;MACKAY, 1981;MILLARD et al, 2001;RICHARDSON, 1967a;STEBBINS, 1968;WULF et al, 1995). Este tema de investigação está vinculado aos resultados de pesquisa que investigaram o próprio efeito da prática mental e combinação de prática.…”
unclassified
“…Observational training [54][55] and mental practice [56][57] are most effective when interspersed with physical practice. Combining physical practice with observational training is referred to as dyad training.…”
Section: Motor Learning Training Strategies Utilized Before Practicementioning
confidence: 99%
“…Various studies have analyzed the effect of different methods of training a motor skill and demonstrated that mentally practicing a motor skill provides some improvement in performance [5], but it does not serve as a replacement for physical practice [6]. Immersive virtual reality environments (IVREs) have been used to augment practice of motor tasks by simultaneously challenging physical and mental performance, particularly in the field of rehabilitation [7,8].…”
Section: Introductionmentioning
confidence: 99%